Slip Effect on Stagnation Point Flow past a Stretching Surface with the Presence of Heat Generation/Absorption and Newtonian Heating - Muhammad Khairul Anuar, Mohamed; Nor Aida Zuraimi, Md Noar; Zulkhibri, Ismail; Abdul Rahman, Mohd Kasim; Norhafizah, Md Sarif; Mohd Zuki, Salleh; Anuar, Ishak (2016)
Present study solved numerically the velocity slip effect on stagnation point flow past a stretching surface with the presence of heat generation/absorption and Newtonian heating. The governing equations which in the form of partial differential equations are transformed to ordinary differential equations before being solved numerically using the Runge-Kutta-Fehlberg method in MAPLE. The numerical solution is obtained for the surface temperature, heat transfer coefficient, reduced skin friction coefficient as well as the temperature and velocity profiles. The flow features and the heat transfer characteristic for the pertinent parameter such as Prandtl number, stretching parameter, heat generation/absorption parameter, velocity slip parameter and conjugate parameter are analyzed and discussed.